Electrical Behaviour and Photovoltaic Performance of Poly (Îµ-caprolactone)-Based Quasi-Solid-State Polymer Electrolyte - A. Y. Razamin, N.; H. Y. Subban, R.; Winie, Tan (International Journal of Engineering and Technology, 2018)
Quasi-solid-state polymer electrolytes based on poly(Îµ-caprolactone) (PCL) and dimethylformamide (DMF) with various concentrations of potassium iodide (KI) were prepared and characterized for their electrical properties and the performance in dye-sensitized solar cells (DSSCs). Incorporation of KI increased the conductivity by 3 order of magnitude from 10-6 to 10-3 Scm-1. The highest conductivity was achieved at 0.2 M of KI. The number, n and mobility, Âµ of ions were calculated by impedance spectroscopy to evaluate the conductivity variation quantitatively. Conduction mechanism of the electrolyte was determined using Jonscherâ€™s universal power law. The conduction mechanism was discussed by comparing the behaviour of temperature dependence of exponent s with existing theoretical models. The small polaron hopping (SPH) model was found to be the model for conduction mechanism of PCL-DMF-KI electrolyte. DSSC with 0.2 M of KI shows the highest photovoltaic performance, Î· of 2.72% with short-circuit current density, Jsc of 5.56 mA cm-2, open circuit voltage, Voc of 0.72 V and fill factor, ff of 69%.Â
Keywords: DMF; DSSC; KI; PCL; Polymer Electrolyte.